2018
DOI: 10.3389/fmars.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

Forcings and Evolution of the 2017 Coastal El Niño Off Northern Peru and Ecuador

Abstract: El Niño events, in particular the eastern Pacific type, have a tremendous impact on the marine ecosystem and climate conditions in the eastern South Pacific. During such events, the accumulation of anomalously warm waters along the coast favors intense rainfall. The upwelling of nutrient-replete waters is stopped and the marine ecosystem is strongly impacted. These events are generally associated with positive surface temperature anomalies in the central and eastern equatorial Pacific. During austral summer 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 49 publications
3
50
0
3
Order By: Relevance
“…The coastal upwelling system off Peru is a place of enhanced level of primary production due to high nutrient supply by wind-driven upwelling (Pennington et al 2006). In March 2017, a decrease of the nearshore wind-driven upwelling along the coast of Peru ( Figure 4.7.3(c)), associated with Ekman pumping changes (Echevin et al 2018), probably reduced the inputs of nutrients to the surface layer, therefore decreasing the production of organic carbon and phytoplankton biomass. Thus, the large-scale atmospheric variability in the eastern Pacific has led to significant modification of the local oceanic/land conditions (i) by warming coastal surface waters and (ii) by enhancing precipitation in the northern Peru and Ecuador, and (iii) by decreasing the upwelling-driven primary production in the coastal ocean.…”
Section: S110mentioning
confidence: 99%
“…The coastal upwelling system off Peru is a place of enhanced level of primary production due to high nutrient supply by wind-driven upwelling (Pennington et al 2006). In March 2017, a decrease of the nearshore wind-driven upwelling along the coast of Peru ( Figure 4.7.3(c)), associated with Ekman pumping changes (Echevin et al 2018), probably reduced the inputs of nutrients to the surface layer, therefore decreasing the production of organic carbon and phytoplankton biomass. Thus, the large-scale atmospheric variability in the eastern Pacific has led to significant modification of the local oceanic/land conditions (i) by warming coastal surface waters and (ii) by enhancing precipitation in the northern Peru and Ecuador, and (iii) by decreasing the upwelling-driven primary production in the coastal ocean.…”
Section: S110mentioning
confidence: 99%
“…The role of equatorial ocean dynamics for the onset of the 2017 coastal warming is a little more controversial. While Rodríguez‐Morata et al () and Hu et al () conclude from the absence of a clear Kelvin wave propagation signal in the thermocline depth anomalies from the Tropical Atmosphere Ocean/Triangle Trans‐Ocean Buoy Network (TAO/TRITON) moored buoy array in the tropical Pacific (Figure ) that equatorial waves were not the dominant forcing mechanism, Echevin et al () and Peng et al () find a contribution of downwelling Kelvin and coastally trapped waves to the development of the warm anomaly in their model experiments and observed sea level anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…cpc.ncep.noaa.gov/products/analysis_monitoring/ensostuff/ONI_v5.php; Echevin et al, 2018). Studies that have investigated the origin of the coastal SST anomaly agree on the important role of anomalous northerly coastal winds (Echevin et al, 2018;Garreaud, 2018;Peng et al, 2019;Rodríguez-Morata et al, 2019). This weakening of the local southeasterly trade winds has in turn been traced back to a weakening of the free tropospheric westerlies impinging the subtropical Andes (Garreaud, 2018) and an anomalous weakening of the middle-upper level subtropical westerly flow (Rodríguez-Morata et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that a minute increase in bottom water oxygen concentration induced by El Niño events would be sufficient in shifting the U(VI)/U(IV) boundary by a few centimeters and remobilize authigenic U (Scholz et al, 2011). Preceding and during our sampling campaign, a coastal El Niño event, with coastal precipitation as strong as the 1997-1998 El Niño event, had developed rapidly and unexpectedly in January and disappeared by May 2017 during cruise M136 (Echevin et al, 2018;Garreaud, 2018;Peng et al, 2019). This strong coastal El Niño event could induce an oxygenation event large enough to remobilize authigenic U along the Peruvian shelf.…”
Section: Lack Of Linear 238 U-salinity Correlation In the Peruvian Omzmentioning
confidence: 87%
“…Alongshore winds were unusually weak off Peru preceding and during our sampling campaign as a result of the 2017 coastal El Niño (Echevin et al, 2018;Lüdke et al, 2020;Peng et al, 2019), which resulted in nominal upwelling in the water column. At nearshore stations, upwelling rates at the base of the ML varied between 1.3 × 10 −7 and 9.7 × 10 −6 m s −1 , whereas upwelling rates at offshore stations were on the order of 10 −10 to 10 −8 m s −1 and essentially negligible.…”
Section: Export Fluxes Of 234 Thmentioning
confidence: 94%